Evolution of Reproductive Division of Labor – Lessons Learned From the Social Amoeba Dictyostelium discoideum During Its Multicellular Development - Dhakshinamoorthy, Ranjani; Singh, Shashi P. (Frontiers in Cell and Developmental Biology, 2021)
The origin of multicellular life from unicellular beings is an epochal step in the evolution of eukaryotes. There are several factors responsible to influence cell fate choices during differentiation and morphogenesis of an organism. Genetic make-up of two cells that unite and fertilize is the key factor to signal the formation of various cell-types in due course of development. Although ploidy of the cell-types determines the genetics of an individual, the role of ploidy in cell fate decisions remains undetermined. Dictyostelium serves as a versatile model to study the emergence of multicellular life from unicellular life forms. In this work, our interest is to understand the influence of ploidy status of a cell on cell fate commitments during Dictyostelium development. We tested our notions by reconstituting Dictyostelium cells of different ploides-one of the haploid parents with its isogenic diploid derivative and allowing them to undergo development. The diploid strains used in this study were generated exploiting the parasexual genetics. The ploidy status of the haploids and diploids were ensured by microscopy, flow cytometry, and karyotyping. Prior to reconstitution, we labelled the cells by two methods. First, intragenic expression of red fluorescent protein (RFP) and second, staining the amoebae with a vital, fluorescent dye carboxyfluorescein succinimidyl ester (CFSE). RFP labelled haploid cells allowed us to track the haploids in the chimeric aggregates, slugs, and fruiting bodies. The CFSE labelling method allowed us to track both the haploids and the diploids in the chimeric developmental structures. Here, we report that ploidy status of a cell could also play a crucial role in regulating the cell fate commitments. Our findings illustrate that the haploids demonstrate sturdy cell fate commitment starting from the aggregation stage. The haploids remain crowded at the aggregation centres of the haploid-diploid chimeric aggregates, at the slug stage haploids are predominantly occupying the posterior regions of the slugs, and are visible in the spore population in the fruiting bodies. Subsequently, our findings conclude that apart from the already reported factors that influence cell fate decisions, during Dictyostelium development, are highly influenced by the ploidy status of a cell.